Synthesis, microstructure, magnetic and electromagnetic behavior of graphene oxide/hexagonal barium ferrite aerogel nanocomposites within the frequency range of 1–18 GHz - Reza Ghorbanpour Ghartavool; Gholam Reza Gordani; Mohammad Reza Loghman Estarki; Majid Tavoosi; Mehdi Mazaheri Forushani; Esmail Kiani (Arabian Journal of Chemistry, 2023)
The fabrication of lightweight graphene oxide aerogel (GOA) composites with barium ferrite (BF) nanoparticles is investigated in this study as a method of shielding electronic and telecommunication equipment from electromagnetic radiation. The effects of various weight percentages of barium ferrite nanoparticles on the microstructure, phase, magnetic characteristics, and wave absorption were investigated. The XRD, FTIR, Raman spectroscopy, X-ray Photoelectron spectroscopy (XPS), thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC), FESEM, and vibrational magnetometry (VSM) and the vector network analyzer (VNA) were used to characterize the sample.Results show that barium ferrite nanoparticles had a saturation magnetization of 42.94 emu/g, whereas graphene oxide aerogel composite containing 67 wt% of barium ferrite nanoparticles had a saturation magnetization of 29 emu/g. The Coercivity of the composite rose when the amount of barium ferrite nanoparticles was reduced. Within the matched frequency of 12.1 GHz and an effective absorption bandwidth (RL < −10 dB) of 2.6 GHz, the graphene aerogel nanocomposite sample with a thickness of 4 mm and 40 wt% of barium ferrite nanoparticles had the highest level of reflection loss (−43 dB).